INTEGRASI PENDIDIKAN AGAMA ISLAM DAN KEADILAN SOSIAL DALAM MENGHADAPI TANTANGAN ERA DIGITAL - Latifah, Latifah .; Hamdanah, Hamdanah; Normuslim, Normuslim (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2026)
This article aims to analyze the integration of Islamic Religious Education (IRE) with the values of social justice in addressing the challenges of the digital era. The rapid development of information technology has brought significant changes in various aspects of life, including the field of education. However, on the other hand, the digital era has also given rise to various social problems such as the digital divide, misinformation, and the weakening of moral and ethical values. In this context, Islamic Religious Education plays a strategic role in shaping students’ character, not only to be religious but also to possess a strong sense of social awareness. This study employs a qualitative approach using a library research method, examining various literature related to Islamic education, social justice, and digital transformation. The findings indicate that the integration of IRE and social justice can be implemented through strengthening value-based curricula, applying contextual learning approaches, and utilizing digital technology in an ethical and responsible manner. In addition, teachers play a crucial role as agents of transformation who are capable of internalizing social justice values in the learning process. These findings confirm that the integration of Islamic Religious Education and social justice is not only relevant but also an urgent necessity in the digital era. With proper integration, Islamic education can serve as an effective instrument in fostering a generation that is not only intellectually competent but also just, empathetic, and possesses integrity in social life.